KEBIJAKAN OPTIMALISASI PENERIMAAN PAJAK WARNET DI KOTA PEKANBARU (STUDI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN TAHUN 2012-2014) - Satria, Harry Nova; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Entertainment tax income from the internet cafes at the region of Simpang Baru, Tampan Regency has not been at maximum level because in the past 3 years of administration, only Rp. 7.354.898 that has been stored to the goverment as entertainment tax from internet cafes .The income of tax is not proportional with the amount of internet cafes that are in the refion of Simpang Baru, Tampan Regency. The main cause of this case is tax infringement by many of the internet cafes that was explained beforehand by the state goverment.The issue of this research is: how does the city administration reacts to the internet cafe phenomenon thats happening in Pekanbaru (Simpang Baru, Tampan Regency Research 2012-2014)?The type of this research is quantitative research, and using interviews, documentation reviews, observation to gather data that is used in this research. The source of data in this research is from primary and secondary datas.The results of this research is, PP No. 5 Year 2011, concerning the Entertainment Tax, is a form of goverment regulation for internet cafes in Pekanbaru City by administration. With this regulation, state goverment can optimize the state income from the entratainment tax. Optimization of the entertainment tax in Simpang baru, Tampan Regency, Pekan Baru is to discipline the tax evading internet cafes by doing pengsan. Techically, the goverment has supervised and has been doing soscialization about the regulation to the community especially internet cafe owners that are residing in Pekan baru, particulary in Simpang baru, because 2 of the biggest universities in Riau is at Simpang Baru, therefore Simpang Baru is a big potential place for internet cafes to thrive.Keywords : Regulation, Optimization, Tax Income, Internet cafe.